2016
DOI: 10.1007/978-3-319-52162-6_52
|View full text |Cite
|
Sign up to set email alerts
|

Information Competencies of Historians as Archive Users: A Slovenia/UK Comparison

Abstract: Abstract. This paper reports a study of the characteristics, skills and competencies of historians, both amateur and professional, as users of archives. It makes two main comparisons: between professional historians and amateurs, typically genealogists and family historians; and between participants in Slovenia and in the United Kingdom. The study is in two parts. First, a detailed and comprehensive literature analysis, including information competencies of archivists where relevant, as well as those of users,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Previous research (e.g. Duff and Johnson, 2003;Yakel and Torres, 2003;Allison-Bunnell et al, 2011;Vilar et al, 2016) have identified amateur historians, e.g. genealogists and local historians, to be common users of archives, but this group is not identified in our material.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Previous research (e.g. Duff and Johnson, 2003;Yakel and Torres, 2003;Allison-Bunnell et al, 2011;Vilar et al, 2016) have identified amateur historians, e.g. genealogists and local historians, to be common users of archives, but this group is not identified in our material.…”
Section: Resultsmentioning
confidence: 91%
“…Previous research identifies historians as an active user group of cultural heritage archives (Duff and Johnson, 2002;Choi and Rasmussen, 2003;Tibbo, 2003;Duff et al, 2004;Zhou, 2008;Chassanoff, 2013Chassanoff, , 2018Sinn and Soares, 2014;Vilar et al, 2016). Other user groups that have been examined are genealogists (Allison-Bunnell et al, 2011;Duff and Johnson, 2003;Hamburger, 2004), film-makers (Treat and Judkins, 2018) and other academics, students and amateur researchers (Hamburger, 2004;Allison-Bunnell et al, 2011;Langa et al, 2023;Weber et al, 2023).…”
Section: Who Are the Users Of Cultural Heritage Archives?mentioning
confidence: 99%
See 3 more Smart Citations